PEMBELAJARAN INTERAKTIF SISTEM TATA SURYA MELALUI AUGMENTED REALITY DALAM PENDIDIKAN DASAR - Awang Pradana; Radiansyah Radiansyah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2026)
This study aims to design and develop interactive learning media based on Augmented Reality (AR) for solar system material, targeting sixth-grade students at SDN 012 Tarakan. The media development was carried out using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. This media was created using the Unity and Vuforia SDK platforms, equipped with 3D objects and audio explanations to aid student understanding. The study involved 26 sixth-grade students through purposive sampling. The material presented included an introduction to the eight planets, the Sun, and the Moon. whereas the functionality test (Blackbox Testing) revealed that 16 application features functioned well. The media expert validation results obtained an average score of 94%, and the material expert validation reached 81.66%, both of which were in the very feasible category. Student responses were also very positive, with an average of 96.09%. Thus, this AR-based learning media is deemed effective, engaging, and suitable for use in the learning process at SDN 012 Tarakan.